Stability of a monovalent rotavirus vaccine after exposure to different temperatures observed in KwaZulu-Natal, South Africa - Asowata, Osaretin Emmanuel (Afr Health Sci, 2019)
BACKGROUND: Rotavirus infection and its associated hospitalization of children less than 5 years old in middle- and low-income countries remains a public health challenge. We hypothesized that the Rotarix®potency is affected by non-optimal temperatures which translates into reduced vaccine effectiveness in these settings. OBJECTIVE: To assess the effect of non-optimal temperatures on the potency of the Rotarix® vaccine in South Africa. METHODS: Rotarix® vaccine was exposed to temperatures reflecting breaches in the cold chain. Vero cells (ATCC CCL-81) grown in a 24-well tissue culture plates were infected with Rotarix® vaccine viruses after exposure to non-optimal temperatures and the potency of the vaccine was determined using the plaque assay. RESULTS: Exposure of the Rotarix® vaccine to seasonal temperatures in KwaZulu-Natal for 6 hours and to extreme temperatures of 40oC for 72 hours as well as to −20°C and −80°C for 12 hours did not affect the potency of the vaccine beyond its expected standard of >7 x 10(5) PFU/ml. CONCLUSION: This study revealed that the Rotarix® vaccine remains potent even after exposure to non-optimal temperatures. However, this study only explored the effect of a constant ‘adverse’ temperature on vaccine potency and not the effect of temperature fluctuations.